Chondroitin Sulfate N‐acetylgalactosaminyltransferase‐1 (CSGalNAcT‐1) Deficiency Results in a Mild Skeletal Dysplasia and Joint Laxity. Issue 1 (22nd September 2016) - Vodopiutz, Julia; Mizumoto, Shuji; Lausch, Ekkehart; Rossi, Antonio; Unger, Sheila; Janocha, Nikolaus; Costantini, Rossella; Seidl, Rainer; Greber‐Platzer, Susanne; Yamada, Shuhei; Müller, Thomas; Jilma, Bernd; et al.
Abstract : We report on the first bi‐allelic loss‐of‐function mutations in CSGALNACT1, that result in joint laxity and skeletal dysplasia with radiographic features typical for Desbuquois dysplasia. The clinical features in GalNAcT‐1 deficiency are milder than those in glycosaminoglycan synthesis defects which are located "upstream" and "downstream" of GalNAcT‐1. This adds to the genetic heterogeneity of Desbuquois dysplasia and confirms the importance of glycosaminoglycan biosynthesis in the pathophysiology of skeletal and connective tissue disorders. ABSTRACT: Mutations in genes encoding enzymes responsible for the biosynthesis and structural diversity of glycosaminoglycans (GAGs) cause a variety of disorders affecting bone and connective tissues, including Desbuquois dysplasia (DD). In an infant with prenatal‐onset disproportionate short stature, joint laxity, and radiographic findings typical for DD compound‐heterozygosity for a large intragenic deletion, and a p.Pro384Arg missense mutation in CSGALNACT1 was found. CSGALNACT1 encodes chondroitin sulfate N ‐acetylgalactosaminyltransferase‐1 (CSGalNAcT‐1, ChGn‐1), which initiates chondroitin sulfate (CS) chain biosynthesis on the so‐called GAG‐protein linker region tetrasaccharide. Biochemical studies revealed a reduced GalNAc‐transferase activity of the Arg‐384 mutant protein, whereas no differences in proteoglycan synthesis in fibroblasts and the GAG content in the urine were found between patient and controls. This is the first description of bi‐allelic loss‐of‐function mutations in CSGALNACT1 that produce a skeletal dysplasia reminiscent of the skeletal dysplasia of Csgalnact1 –/– mice, and adds to the genetic heterogeneity of DD.